Suprascapular neuropathy in a collegiate baseball player - Niemann, A. J.; Juzesyn, L. S.; Kahanov, L.; Eberman, L. E. (Asian Journal of Sports Medicine, 2013)
Background: Suprascapular neuropathy (SSN) is generally thought of as a diagnosis of exclusion. However, increasing attention is being paid to the diagnosis, treatment and rehabilitation of this pathology to prevent chronic supraspinatus and infraspinatus atrophy in patients. To date, literature has only articulated variable or customized treatment and rehabilitation plans without clear standardized care. This case study provides a detailed description of the diagnosis, treatment, and rehabilitation of a collegiate baseball player`s recovery from suprascapular nerve release.